Effects of ultraviolet radiation and CO2 increase on winter phytoplankton assemblages in a temperate coastal lagoon - Domingues, Rita B. (2015)
Increases in ultraviolet radiation (UVR) and CO2 affect phytoplankton growth and mortality in a variety of different ways. However, in situ responses of natural phytoplankton communities to climate change, as well as its effects on phytoplankton annual cycles, are still largely unknown. Although temperature and UVR have been increasing in temperate latitudes during winter, this season is still particularly neglected in climate change studies, being considered a non-active season regarding phytoplankton growth and production. Additionally, coastal lagoons are highly productive ecosystems and very vulnerable to climate change. This study aims, therefore, to evaluate the short-term effects of increased UVR and CO2 on the composition and growth of winter phytoplankton assemblages in a temperate coastal lagoon. During winter 2012, microcosm experiments were used to evaluate the isolated and combined effects of UVR and CO2, under ambient and high CO2 treatments, exposed to ambient UV levels and photosynthetically active radiation (PAR), or to PAR only. Phytoplankton composition, abundance, biomass and photosynthetic parameters were evaluated during the experiments. Significant changes were observed in the growth of specific phytoplankton groups, leading to changes in community composition. The cyanobacterium Synechococcus was dominant at the beginning of the experiment, but it was negatively affected by UVR and CO2. Diatoms clearly benefited from high CO2 and UVR, particularly Thalassiosira. Despite the changes observed in specific phytoplankton groups, growth and production of the whole phytoplankton community did not show significant responses to UVR and/or CO2.